Respostas

2014-06-10T20:16:33-03:00
Na verdade é um sistema de equação!

{x-y=4
{x+y=2

      x - y = 4
      x + y = 2       (somar)

      x - y = 4
+    x + y = 2
----------------
    2x + 0 = 6

  2x = 6
x = 6/2
x = 3           agora achar o valor de (y)

x - y = 4         para x = 3
3 - y = 4
- y = 4 - 3
- y = 1
y = - 1

VERIFICAÇÃO
para
x = 3
y = - 1

{x-y=4 
3-(-1) = 4
3 + 1 = 4
     4 = 4
 
{x+y=2

3 - 1 = 2
    2 = 2



outra maneira de resolver

{x-y=4
{x+y=2

x - y = 4
x = 4 + y      (substituir o (x))

       x + y = 2
(4 +y)+ y = 2
4 + y + y = 2
2y + 4 = 2
2y = 2 - 4
2y = - 2
y = -2/2
y = - 1        agora achar o valor de (x)

x = 4 + y
x = 4 - 1
x = 3




1 5 1